TEACHER MADE ASSESSMENT AUTHENTICITY IN SENIOR HIGH SCHOOLS AND ITS CONTRIBUTION TO STUDENTSâ ENGLISH ACHIEVEMENT - Paragae, I G.A.P.N.S.; Marhaeni, A.A.I.N; Dantes, Nyoman (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract The present study aims at analyzing the authenticity of teacher made assessment in State Senior High Schools in Buleleng Regency in terms of assessment planning, assessment implementation as perceived by teachers and students and the studentsâ English achievement. It also investigates assessment contribution to studentsâ English achievement. The mixed method design research took 32 English teachers and 32 classes of students as the sample. The data were gained by collecting assessment documents, administering questionnaires and interview. The study found that the assessment have high authenticity level of planning, high authenticity level of implementation as perceived by teachers and high authenticity level of level implementation as perceived by students. The studentsâ achievement after being assessed by using their teacher made assessment is considered high. The study also confirmed that there is a significant contribution of the authenticity of teacher made assessment to studentsâ English achievement. More specifically, assessment implementation as perceived by students gives the highest contribution. Keywords: authenticity, teacher made assessment, English achievement